Avaliação do desempenho ambiental da fase agrícola no sistema de produto biodiesel de soja no Rio Grande do Sul - Maciel, Vinícius Gonçalves (2014)
Nowadays, the use of biomass for biofuel production is a widely discussed issue, mainly because of environmental impacts. Soybeans are the main raw material used for the Brazilian biodiesel production, and Rio Grande do Sul is one of the largest producers of soybean in Brazil and the world. Its importance is due mainly because of its versatility, being employed, also, for example, in food, agricultural and chemical industries. However, there are no studies of the environmental performance of the soy produced in the state of Rio Grande do Sul. In this scenario, the Life Cycle Assessment is presented as a tool to evaluate the environmental performance. Therefore, this paper presents an assessment of the environmental performance of the soy produced in the state of Rio Grande do Sul, from the construction of an representative life cycle inventory of the study area. The study was conducted from cradle to gate of the farm from specific primary data for the steps which are the main link in the production of soybeans in the Rio Grande do Sul, on the 2012/2013 harvest. Secondary data were obtained from the literature and databases available on SimaPro® software. The inventory data were collected in 23 municipalities that together account for 32% of total production of soybean state. Alternative scenarios for change land use change show emission values ranging from 0.03 to 1.03 eq.ha-1 t CO2. The Life Cycle Assessment was conducted from these data and the normalized score calculated from the CML 2001 method revealed a significant contribution seeding and fertilization stage due to the use of phosphate fertilizer. The potential for global warming was largely influenced by the Land Use Change.